An investigation into beaver-induced Holocene sedimentation using ground penetrating radar and seismic refraction: Beaver Meadows, Rocky Mountain National Park - Kramer, Natalie, author; Wohl, Ellen, advisor; Harry, Dennis, advisor; Meiman, Paul, committee member (Colorado State University. Libraries, 2011)
This study used ~1 km of near-surface seismic refraction (SSR) data and ~6 km of ground penetrating radar (GPR) data to infer the impact of Holocene beaver activity on sediment aggradation in Beaver Meadows, Rocky Mountain National Park. GPR data were used to uniquely identify radar packages of genetically related strata corresponding to glacial, non-glacial, and beaver-induced sedimentation. The radar package relating to glacial deposition was wedge-shaped and predominantly composed of a diffraction-rich, chaotic facie. The radar package relating to alluvium was draped over the glacial deposits and was characterized by multiple facies, but in general contained complex, slightly continuous reflectors interfingered with continuous, horizontal to subhorizontal reflectors. The radar package related to beaver-induced sedimentation was characterized by a laterally continuous parallel facie, interpreted to be ponded sediment, that abruptly truncated into a zone of chaotic reflectors, interpreted to be a beaver dam. In order to determine the relative magnitude of post-glacial deposition, the bedrock contact was determined using seismic refraction, GPR, auger data, and previous seismic and drilling studies. This study concludes that beaver damming is an important aggradational process trapping sediments within the Holocene, but did not cause significant amounts of aggradation. Beaver-induced sediments constituted ~50 percent of the alluvium, but the alluvium only constituted ~15 percent of the total valley fill, with a mean depth of ~1.3 m. The thin veneer of Holocene sedimentation implies that Beaver Meadows is not a site of continuous sediment deposition, but rather one characterized by episodic temporal and spatial aggradation, punctuated by incision, re-working and exhumation.
Keywords: ground penetrating radar; beaver; Holocene; Rocky Mountain National Park; sediment; seismic refraction